2008
DOI: 10.1097/iae.0b013e318169faee
|View full text |Cite
|
Sign up to set email alerts
|

Diode Laser Treatment of Retinopathy of Prematurity

Abstract: DLPC is a safe and effective treatment for ROP. Neonates of lower gestational age and birth weight require earlier and more aggressive laser treatment and may have a higher refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 31 publications
13
53
3
7
Order By: Relevance
“…Here the anatomic success rate for referred patients was 93%; however, the anatomic success rate for non-referred patients was 100%. The overall anatomic success rate in our clinic was 96.1%, and this rate is consistent with previous studies, which have reported success rates above 90% (10)(11)(12)(13)(14)(15) . Thus, we found a significantly better success rate in the non-referred group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here the anatomic success rate for referred patients was 93%; however, the anatomic success rate for non-referred patients was 100%. The overall anatomic success rate in our clinic was 96.1%, and this rate is consistent with previous studies, which have reported success rates above 90% (10)(11)(12)(13)(14)(15) . Thus, we found a significantly better success rate in the non-referred group.…”
Section: Discussionsupporting
confidence: 92%
“…Low BW and small GA are known to be risk factors for the development of ROP (18) . Many previous studies included treatment groups mainly consisting of preterm patients weighing <1000 g and aged <28 weeks (10,(19)(20)(21) . In our study, consistent with previous reports, the average BW and GA in patients who received treatment were 900 g and 27 weeks, respectively; although these values were higher among referred patients, they were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,17 Our study and other case series found a lower SE in patients treated with IVB than in patients treated with cryotherapy (range, À 6.5 to À 3.51 D) or with laser peripheral ablative therapy (range, À 4.71 to À 1.50 D). [3][4][5][6][7] Our prevalences of myopia and high myopia are also similar to those of preschool-age patients in a recent case series who were treated with IVB only (55.6% and 11.1 to 17.0%) ( Table 3). 9,10,17 In the current study, the prevalences of myopia and high myopia increased significantly with the severity of ROP but were not associated with AXL changes.…”
Section: Eyesupporting
confidence: 81%
“…The reported rates range from 55.2 to 80.4% and 23.9 to 31.5%, respectively (Table 3). 3,4,6 The reported rates of myopia and high myopia were even higher in patients treated with cryotherapy, ranging from 82.9 to 92.0% and 32.0 to 52.5%, respectively (Table 3). [5][6][7] In the current study, the percentages of patients with myopia and high myopia among IVB-treated patients were 47.5 and 10.0%, respectively, which are less than the previously reported percentages for patients treated with laser treatment or cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation